“Make Resilience Matter” for Children Exposed to Intimate Partner Violence Project: Mobilizing Knowledge to Action Using a Research Contributions Framework - Alaggia, Ramona; Morton, Sarah; Vine, Cathy (International Journal of Child and Adolescent Resilience / Revue internationale de la résilience des enfants et des adolescents)

(untitled) (Canada Research Chair in Interpersonal Traumas and Resilience/Chaire de recherche du Canada sur les traumas interpersonnels et la résilience, 2019)
Objective: This article describes using a Research Contribution Framework (RCF) (Morton, 2015a), to plan and document the progress of knowledge mobilization (KMb) efforts for the Make Resilience Matter (MRM) for Children Exposed to Intimate Partner Violence (IPV) study. Research uptake, use and impact activities were planned for this project designed to identify how to foster resilience-informed practice with children exposed to IPV. This KMb strategy is useful for planning and considering how we engage knowledge users, context, environmental impact, unexpected developments, and the complexities of doing research and mobilizing results in the “real world” of practice. The benefits of mapping RCF onto KMb planning and lessons learned may be transferred to other projects. Method: First we outline RCF; second, we describe the MRM project; third we apply RCF to the MRM project detailing a process for engaging knowledge users and planning and tracking research uptake, use and impact. The trans-theoretical theory of change (Prochaska & DiClemente, 1982) is used to understand readiness to change in relation to research uptake and use. An overarching feminist theoretical understanding of gender based violence (Hawkesworth, 2006; Heise, 1998) helps to inform our awareness of the socio-political context. Results: Research uptake, use, and impact as applied to the MRM project are presented. An outcomes chain (Morton, 2015a) is offered to help trace engagement/involvement, activities/outputs, awareness/reactions, knowledge/attitudes, and anticipated practice behaviour change. Four guiding principles emerged from our experience which may helpto inform future KMb efforts.